2023
DOI: 10.1021/acsanm.3c03483
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Few-Layer Bismuthene for Efficient Electroreduction of CO2 to Formate

Xian Wang,
Dezhong Song,
Chunxiu Wang
et al.

Abstract: Bismuth (Bi) nanosheets are considered an auspicious electrocatalyst for CO 2 reduction. Herein, we report a facile bottom-up synthesis toward few-layer bismuthene (f-bismuthene) with a hydrophobic surface, which shows high activity over a wide potential window of 400 mV and maintains over 80.4% formate Faradaic efficiencies (FE formate ) after 45 h in an H-type electrolytic cell. Remarkably, the f-bismuthene achieves a maximum formate partial current density of 419.4 mA cm −2 and FE formate of 96.9% in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Zhang et al showed that mass transport could also be facilitated by the nanoconfinement effect using bismuth nanorods filled in nitrogen-doped carbon nanotubes . Various bismuth nanostructures, such as Bi dendrites, , two-dimensional (2D) nanosheets, and nanoflowers, have been prepared by electrodeposition, hydrothermal methods, and in situ morphology reconstruction techniques. It was demonstrated that the increased edge sites on bismuth nanosheets could enhance CO 2 adsorption and facilitate CO 2 RR to formate .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al showed that mass transport could also be facilitated by the nanoconfinement effect using bismuth nanorods filled in nitrogen-doped carbon nanotubes . Various bismuth nanostructures, such as Bi dendrites, , two-dimensional (2D) nanosheets, and nanoflowers, have been prepared by electrodeposition, hydrothermal methods, and in situ morphology reconstruction techniques. It was demonstrated that the increased edge sites on bismuth nanosheets could enhance CO 2 adsorption and facilitate CO 2 RR to formate .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research efforts have been devoted to various extensively investigated metal catalysts such as In, Bi, Sn, and Pb for CO 2 RR to formate. , Among them, Bi-based catalytic materials are particularly appealing with the advantages of environmental friendliness, low-cost, and especially high formate production performance. Nevertheless, developing highly efficient and stable catalysts for formate production is of significance and a cutting-edge topic. Strategies such as the fabrication of Bi nanosheets and Bi-O-M, exposure of specific facets, , and doping with other elements have been developed to improve the performance of Bi-based catalysts. Shen et al synthesized Cu-doped Bi nanosheet bimetallic catalysts, which show impressive catalytic performance for formate production .…”
Section: Introductionmentioning
confidence: 99%